Standard Establishment to Improve Performance Implementation of Standards of Internal Quality Assurance Systems of Private Universities (IQSA PU) - Abdus Syukur, Imron; Suherman, Dadang; Gaffar, M. Andriana; Mardiana, Dinny (CV. Inara, 2022)
The title of this research is :